Blackberry summer eaudiobook Hope's crossing series, book 1. - Thayne, RaeAnne (Hope's Crossing, 2016)
New York Times bestselling author RaeAnne Thayne brings readers another heartwarming story of community and romance in Blackberry Summer , the first book in the Hope's Crossing series. Claire Bradford needed a wake-up call. What she didn't need was a tragic car accident. As a single mom and the owner of a successful bead shop, Claire leads a predictable life in Hope's Crossing, Colorado. So what if she has no time for romance? At least, that's what she tells herself, especially when her best friend's sexy younger brother comes back to town as the new chief of police. But when the accident forces Claire to slow down and lean on others—especially Riley McKnight—she realizes, for the first time, that things need to change. And not just in her own life. The accident—and the string of robberies committed by teenagers that led up to it—is a message to the people of Hope's Crossing. The sense of community and togetherness had been lost during those tough years. But with a mysterious "Angel of Hope" working to inspire the town, Riley and Claire will find themselves opening up to love and other possibilities by the end of an extraordinary summer ...